Delayed Diagnosis and Multi-TKI Intolerance: A Case Report of CML Concurrent With COVID-19 - Luan, Chengxin; Wang, Haixia; Zhou, Junjie; Ma, Xiaoyu; Long, Zhangbiao; Cheng, Xin; Chen, Xiaowen; Xia, Ruixiang; Ge, Jian (Frontiers in Oncology, 2022)
Introduction The hematological manifestations of corona virus disease 2019 (COVID-19) can confound diagnosis and therapy of other diseases. In this paper, we firstly reported a case of chronic myeloid leukemia (CML) of delayed diagnosis and intolerance to tyrosine kinase inhibitors (TKIs) concurrent with COVID-19. Case presentation A 56-year-old female was diagnosed as COVID-19 with no obvious leukocytosis(WBC≤17 ×109 /L) or splenomegaly until ablation of the virus. Bone marrow aspiration was conducted to establish diagnosis of CML. She accepted adjusted dosage of imatinib initially and had to suspend it after myelosuppression (d41). After hematopoietic therapy, imatinib was given again(d62) but she was still intolerable and nilotinib 150mg twice a day was prescribed from d214. But just about four weeks later, nilotinib was discontinued due to myelosuppression and reduced nilotinib 150mg per day was re-initiated (d349), while she still be intolerant to it. Similarly, from day398 flumatinib 200mg per day was tried but she was intolerable. Her white blood cell or platelet count fluctuated markedly with poor therapeutic response. Considering that she was relatively tolerant and responsive to imatinib, the medication was re-initiated at 200mg and reduced to 100mg per day. Her follow-up revealed stable WBC and PLT. The latest BCR-ABL-210/ABL was decreased to 0.68% % about 6 months after imatinib re-initiated, which means improved response . Conclusion The offset effect between CML and SARS-CoV-2 infection was supposed to be the underlying mechanism for the absence of leukocytosis or splenomegaly. The impact of immune network by SARS-CoV-2 preserved and disrupted the patient’s response to TKIs though the virus’ ablation. We suggest that continued elevation of basophils may be a useful indicator for CML concurrent with COVID-19 and individualized treatment with adjusted dosage and suitable type of TKIs should be considered to improve the patient’s health outcome.